Sulfathiazole-based novel UV-cured hydrogel sorbents for mercury removal from aqueous solutions - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Sulfathiazole-based novel hydrogel sorbents P(Sulti/hydroxyethyl methacrylate (HEMA)/acrylic acid (AAc)) were prepared by UV irradiation and used for the removal of mercury(II) ion from aqueous media. Hydrogels have been characterized by SEM and thermogravimetric analysis (TGA) techniques. The influence of the uptake conditions was investigated; maximum Hg(II) ion adsorption capacity obtained was 13.46 +/- 1.15mg g(-1) at pH 5.0. The hydrogels were tested several times without loss of adsorption capacity. The selectivity of the hydrogel towards to Hg(II), Cd(II) and Zn(II) ions tested was Hg>Cd>Zn. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mercury; Hydrogel; Glycidyl methacrylate-sulfathiazole adduct; UV-curing; Adsorption; SELECTIVE BINDING; HEAVY-METALS; WASTE-WATER; RESINS; ACID; RECOVERY; POLYMERS; IONS